Taiwan's Travel and Border Health Measures in Response to Zika - Ho, Li-Li (Health Secur, 2017)
Zika virus has recently emerged as a worldwide public health concern. Travel and border health measures stand as one of the main strategies and frontline defenses in responding to international epidemics. As of October 31, 2016, Taiwan has reported 13 imported cases, 5 of which were detected through routine entry screening and active monitoring at international airports. This article shares Taiwan's disease surveillance activities at designated points of entry and travel and border health measures in response to Zika. The Taiwan government collaborates with its tourism industry to disseminate information about precautionary measures and encourages tour guides to report suspected individuals or events to activate early response measures. Taiwan also engages in vector control activities at points of entry, including targeting aircraft from countries where vector-borne diseases are endemic, implementing mosquito sweep measures, and collecting vector surveillance data. In future emerging and reemerging disease events, entry surveillance at designated points of entry may enable early detection of diseases of international origin and more rapid activation of public health preparedness activities and international collaboration. Taiwan will continue to maximize border and travel health measures in compliance with IHR (2005) requirements, which rely on continued risk assessment, practical implementation activities, and engagement with all stakeholders.